Atlanta 1864 : last chance for the Confederacy - McMurry, Richard M. (Great campaigns of the Civil War., 2000)
The author presents the situation "as federal armies under William T. Sherman contended with Joseph E. Johnston and his successor, John Bell Hood, and moved steadily through Georgia to occupy the rail and commercial center of Atlanta."--Jacket